A Pediatrician's Guide to Postdischarge Nutrition in NICU Graduates - Kimberly Ernst (Association of American Medical Colleges, 2009)
Abstract Introduction Postdischarge nutrition is important for both growth and development, yet neonatal intensive care unit (NICU) graduates are often quickly taken off their special postdischarge formulas or human milk fortification. This resource was developed to stress the importance of the role of the follow-up physician in ensuring these infants continue to receive their special diets for the appropriate time frame postdischarge. Methods This resource contains a case-based PowerPoint lecture approximately 40 minutes long, followed by a 10-minute Q&A session. All participants receive a handout at the beginning of the lecture for reference. The handout does not include the entire presentation, instead highlighting important points that the audience should take home. Successful implementation is encouraged through an interactive session with the participants using the case-based method of teaching. Results This resource was presented at the University of Oklahoma Department of Pediatrics Annual CME Conference in 2009. Conference participants felt the materials were interesting and helped them understand the importance of their role in encouraging appropriate nutrition postdischarge. Regarding the different scenarios physicians face when working with families of neonatal infants, one pediatrician said afterwards, "You nailed not just one, but every issue on the head." Discussion This resource could be used along with an audience response system or with another case presentation in which the infant receives human milk fortified with additional calories, vitamins, and minerals in order to solidify participants' understanding of postdischarge nutrition for those infants receiving human milk, the preferred food for all infants.